Body Composition, Characteristics, and Basal Metabolic Rate in Male Sports Students - Dewi Fa'iqotul Latifah; Yetty Septiani Mustar; Mokhamad Nur Bawono (Journal of Physical Education Health and Sport, 2026)
The digital lifestyle has led to an increase in sedentary behavior among sports students, which affects their body composition and metabolic status. An imbalance between physical activity and energy intake can alter the BMR (Basal Metabolic Rate). However, descriptive data on these variables among sports students remain limited. This study aims to describe body composition characteristics and Basal Metabolic Rate (BMR) in male sports students, and to illustrate the relationship between BMR and various body composition parameters. This study used a quantitative descriptive design with a cross-sectional approach. The study subjects consisted of 18 male sports students aged 18–23 years. Body composition measurements included Body Mass Index (BMI), Percent Body Fat (PBF), Body Fat Mass (BFM), Fat-Free Mass (FFM), Total Body Water (TBW), and Basal Metabolic Rate (BMR) using the InBody 370 device based on bioelectrical impedance analysis (BIA). The data were analyzed using descriptive statistics and presented as means, category percentages, and a correlation matrix. Results: 66.67% of sports students had a BMR in the normal range, 16.67% in the low range, and 16.67% in the high range. In general, most body composition parameters were within the normal range, with a predominance of fat- free mass. Correlation analysis showed that BMR had a very. strong relationship with FFM and TBW, a strong relationship with BMI, a moderate relationship with BFM, and a weak relationship with PBF. Most male sports students had relatively normal body composition profiles and BMR. BMR in this group was mainly influenced by active metabolic tissue components, particularly fat-free mass and total body water.